The Comparative Genomics and Phylogenomics of Leishmania Amazonensis Parasite. (January 2014) - Tschoeke, Diogo A.; Nunes, Gisele L.; Jardim, Rodrigo; Lima, Joana; Dumaresq, Aline S. R.; Gomes, Monete R.; De Mattos Pereira, Leandro; Loureiro, Daniel R.; Stoco, Patricia H.; De Matos Gliedes, Herbert Leonel; De Miranda, Antonio Basilio; Ruiz, Jeronimo; et al.
Leishmaniasis is an infectious disease caused by Leishmania species. Leishmania amazonensis is a New World Leishmania species belonging to the Mexicana complex, which is able to cause all types of leishmaniasis infections. The L. amazonensis reference strain MHOM/BR/1973/M2269 was sequenced identifying 8, 802 codifying sequences (CDS), most of them of hypothetical function. Comparative analysis using six Leishmania species showed a core set of 7, 016 orthologs. L. amazonensis and Leishmania mexicana share the largest number of distinct orthologs, while Leishmania braziliensis presented the largest number of inparalogs. Additionally, phylogenomic analysis confirmed the taxonomic position for L. amazonensis within the "Mexicana complex", reinforcing understanding of the split of New and Old World Leishmania. Potential non-homologous isofunctional enzymes (NISE) were identified between L. amazonensis and Homo sapiens that could provide new drug targets for development.